Management of tropical secondary rain forest in Latin América, Todays challenges, tomorrows accomplished fact!? / Peter Sips - Sips, Peter (1992)
Tropical, secondary rain forests, definition of tropical secondary rain forest, origin, extent and rates of formation, secondary succession, characteristics of tropical secondary rain forests, values of tropical secondary rain forests; management of tropical secondary rain forests, points to consider, general managements alternatives, some experiments, experiments, with natural regeneration, the Trinidad tropical shelter wood system in costa Rica natural regeneration in florencia sur, Turrialba, costa Rica; suitability of the systems used in the experiments, suitability of the natural regeneration method, suitability of the line planting method and the recur- method, sequence of silvicultural treatments.